ANALISIS EFEKTIVITAS PELAYANAN PUBLIK DI BIDANG PERTANAHAN TERHADAP PENERAPAN STANDAR PELAYANAN PERTANAHAN PADA KANTOR PERTANAHAN KOTA YOGYAKARTA - , SRIYANTI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research is aimed to determine the effectiveness of land services to the land service standard at Yogyakarta Land Office and to find out the factors influence on it. Effectiveness of land services is measured using five indicators : speed of service, efficiency, clarity and certainty of service, comfort and convenience. This is in accordance with the assessment of the effectiveness of the public service based on the opinions of experts such as Tjiptono (2002) and the decision of the Minister for Administrative Reform Number 81 in 1995. The data used in this research were primary data and secondary data at Yogyakarta Land Office study of 2013. Data was collected through interviews, observation, documentation and analysis. Data collection from this research were analyzed by qualitative method. Qualitative research is intended to describe the data according to the studied variables without testing the hypothesis and qualitatively described to obtain an overview of the standard implementation related to land services at Yogyakarta Land Office. The results show that land services at the Yogyakarta Land Office has been effective in terms of speed of service and clarity and certainty service. This model applicable to services land which the processes of its completion simple, i.e. services that involve only one Section. The application of the standard service of land turned out to be insignificant in the achievement of the effectiveness of the services of lands. It can be seen from the efficiency, speed of service, clarity and certainty of the service which has not been achieved, but in terms of ease and comfort is good. Furthermore in term of the implementation of the standard of land service there were two factors that influence land use service has not optimal yet in Yogyakarta Land Office. The first factor was the procedure which requires a number of completeness that should take care of through tables before entering the Land Office. The second factor was human resources that still lack the number of officials who handle the entance documents so that the tardiness of service maintenance is often happened in the file completion. While the organizational structure factors, coordination and communication factors and motivational factors has supported the creation of effective public services.